Indexing for maximum investment results - Neubert, Albert S. (Chicago : Glenlake : Fitzroy Dearborn, 1998)
"Twenty-four years after investment managers decided to implement the S&P 500 indexing strategy, the verdict is in - indexing is the way to go! The first indexers beat over 99% of all actively managed stock funds. In the last ten years, funds based on the S&P 500 have outperformed over 80% of all mutual funds. Today almost 10% of the total market value of all stocks traded in the U.S. is indexed to the S&P 500."--BOOK JACKET. "This book covers all aspect of indexing by leading experts."--BOOK JACKET.
Ch. 1. Why the Case for Indexing Remains Strong -- Ch. 2. Benchmarks: Definitions and Methodologies -- Ch. 3. The First Index Mutual Fund -- Ch. 4. Optimal Indexing -- Ch. 5. Enhanced Indexing - Without Enhanced Risk? -- Ch. 6. Choosing a Benchmark -- Ch. 7. The "S&P Effect" Has Moved Beyond the S&P Composite -- Ch. 8. The S&P500 is Not Your Father's Index -- Ch. 9. Performance Track Record versus Active Management -- Ch. 10. Overview of the Equity Index Fund Marketplace -- Ch. 11. Implementing Equity Index Portfolios -- Ch. 12. Adding Value Through Equity Style Management -- Ch. 13. Using Style Analysis to Build Completeness Funds -- Ch. 14. Index Shares -- Ch. 15. Fixed-Income Indexing -- Ch. 16. The Tax Advantages of Indexing -- Ch. 17. Optimizing Performance -- Ch. 18. The Licensing of Financial Indexes: Implications for the Development of New Index-Linked Investment Products.
Includes bibliographical references and index.
Keywords: Index mutual funds; Investments -- United States; Stock index futures -- United States